Pengaruh Pelatihan dan Kinerja Terhadap Produktivitas Kerja Karyawan Pada Badan Pertanahan Nasional Jakarta Timur - Nabilla Yusman; Irwin Sukrisno Sugeng (Prisani Cendekia, 2023)
With the implementation of correct and appropriate training, companies can improve the performance of employees in achieving predetermined work productivity. This study aims to determine how big the